2022
DOI: 10.1038/s41467-022-28183-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide-based membranes with structural homogeneity for ultrafast molecular sieving

Abstract: Thin-film composite membranes formed by conventional interfacial polymerization generally suffer from the depth heterogeneity of the polyamide layer, i.e., nonuniformly distributed free volume pores, leading to the inefficient permselectivity. Here, we demonstrate a facile and versatile approach to tune the nanoscale homogeneity of polyamide-based thin-film composite membranes via inorganic salt-mediated interfacial polymerization process. Molecular dynamics simulations and various characterization techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(40 citation statements)
references
References 48 publications
(53 reference statements)
1
39
0
Order By: Relevance
“…An increase in the reaction rate can well match these goals, for example, by adding acid acceptors, , increasing reaction temperature, , and adding other comonomers . One can also control the diffusion of PIP (activator) and change the interfacial tension by adding chemicals such as PVA, salts, , and surfactants , to the PIP solution and coating a hydrophilic gel layer on the substrate …”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 99%
“…An increase in the reaction rate can well match these goals, for example, by adding acid acceptors, , increasing reaction temperature, , and adding other comonomers . One can also control the diffusion of PIP (activator) and change the interfacial tension by adding chemicals such as PVA, salts, , and surfactants , to the PIP solution and coating a hydrophilic gel layer on the substrate …”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 99%
“…The development of effective separation technology is one of the ways to relieve environmental pressure. Membrane separation has attracted widespread attention in the field of separation technology due to its simplicity, high efficiency, energy saving, and environmental protection. In this context, a variety of polymer materials have been developed for separation membranes. , Among them, polyamide is one of the most widely used membrane materials due to their high chemical stability, strong mechanical strength, and innately hydrophilic feature, which has exhibited pressure compaction resistance, wide pH operating range, and superior water flux during nanofiltration or reverse osmosis operation. , However, traditional polyamide membranes are amorphous and possess a large amount of nonuniformly distributed free volume pores, which limit the further improvement of inefficient permselectivity . To overcome this disadvantage, developing polyamide materials with well-ordered porous structures is highly desired for the fabrication of high-performance membranes …”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, traditional polyamide membranes are amorphous and possess a large amount of nonuniformly distributed free volume pores, which limit the further improvement of inefficient permselectivity. 8 To overcome this disadvantage, developing polyamide materials with well-ordered porous structures is highly desired for the fabrication of high-performance membranes. 9 To reach this goal, covalent organic frameworks (COFs) may offer an effective platform.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that narrowing the pore size distribution can greatly improve the separation selectivity of nanofiltration membranes, the effect of the pore size distribution on their antifouling performance is still mysterious. Li et al have found that the nanofiltration membranes with different pore size distributions (i.e., NF270 and NF10) showed different fouling behaviors for polycyclic aromatic hydrocarbon micropollutants, that is, the nanofiltration membrane with a wider pore size distribution showed more serious fouling potential, and the larger pores were more easily fouled due to a higher local permeation flux.…”
Section: Introductionmentioning
confidence: 99%